Membumikan Teologi Islam dalam Kehidupan Modern (Berkaca dari Mohammed Arkoun) - Latif, Muhaemin (BINA' AL-UMMAH, 2015)
This article discusses the ideas of Islamic theology in relation to modern life. The main purpose of this article is to present the idea of Mohammed Arkoun, the Algerian contemporary intellectual, to review the classical Islamic theological portrait which tends to stagnant and did not deal with the development of human civilization. The method used in this writing is to employ a qualitative method of research literature. The author of this article comes to conclude that the classical Islamic theology thoughts still focuses on medieval themes. Arkoun, in this sense, offers a reconstruction of Islamic thought that theology can be grounded in the modern life.